Performance of strut-reinforced Kagome truss core structure under compression fabricated by selective laser melting - Gautam, Rinoj (2019)
Lattice structures are regarded as an excellent candidate for lightweight applications owing to their high specific strength and stiffness. In this paper, a novel lattice design is proposed, and its compressive properties are investigated. The Kagome lattice design is modified to form a new lattice core structure, namely, strut reinforced Kagome (SRK) with the presence of extra vertical strut. Ti-6Al-4V SRK unit structures with different aspect ratio are fabricated through selective laser melting. The compressive properties, elastic modulus and peak strength are predicted using analytical solution and are compared with the finite element analysis results and experimental measurements. The SRK unit structures outperformed Kagome unit structures of the same relative density by 13.42% and 12.87% in terms of peak strength and effective modulus, respectively. The sub-β-transus heat treatment on the SRK and Kagome unit structure has led to an increase in the effective moduli, ductility, and energy absorption with a slight decrease in the peak strength.